2015
DOI: 10.4314/jab.v88i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge associated with the production of starters culture used to produce Beninese opaque sorghum beers

Abstract: Objective: The present study aims to document the indigenous Knowledge associated with the production of starters culture to be used for opaque sorghum beers manufacturing in Benin Methodology and results: A quantitative survey was carried out in the central and the northern regions of Benin. A total of ninety (90) processors of traditional beers were interviewed using a semi-structured questionnaire. The collected information was related to the processing method of the starters' production, its shelf life as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The primary source of human infections is ingesting contaminated food [ 33 ]. Indeed, pathogenic bacteria such as staphylococci and Enterobacteriaceae have been identified in African fermented cereal foods [ 34 ] and traditional fermented drinks [ 15 ]. Our study showed that the percentages of samples contaminated with these microorganisms were 60.64% of Enterobacteriaceae and 39.36% of staphylococci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary source of human infections is ingesting contaminated food [ 33 ]. Indeed, pathogenic bacteria such as staphylococci and Enterobacteriaceae have been identified in African fermented cereal foods [ 34 ] and traditional fermented drinks [ 15 ]. Our study showed that the percentages of samples contaminated with these microorganisms were 60.64% of Enterobacteriaceae and 39.36% of staphylococci.…”
Section: Discussionmentioning
confidence: 99%
“…Although lactic acid bacteria can reduce the levels of pathogenic bacteria present in the drinks [ 7 , 8 , 12 , 13 ], some bacteria such as Enterobacter sakazaki , Klebsiella pneumonia , Escherichia coli , and Staphylococcus aureus remain resistant to the acidic environment and cooking process of the fermented foods [ 14 ]. Enterobacteriaceae in Tchoukoutou , sold in northern Benin, has been reported [ 15 ]. It is concerning that the bacteria found in beer can lead to food spoilage [ 16 , 17 ] and negatively impact individuals with health conditions or habitat disorders, such as sepsis, meningitis, endocarditis, peritonitis, or heart disease [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stains used for the antimicrobial test were composed of 12 references strains ( Staphylococcus aureus ATCC 29213, S. epidermidis T22695, Proteus mirabilis A24974, P. vulgaris A25015, Micrococcus luteus , Streptococcus oralis , Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, E. coli O157: H7 ATTC 700728, Salmonella typhi R 30951401 , Candida albicans MHMR, and Pseudomonas aeruginosa ATCC 27853), 15 clinical and food isolated methicillin resistance S. aureus (MRSA), 2 extended-spectrum beta-lactamase E. coli strains, and 11 lactic acid bacteria isolated previously from “tchoukoutou” [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Benin, the starter of the most popular traditional sorghum beer named “tchoukoutou” is reported to be used to cure several infections such as stomach pains and diarrhea [12]. However, a part of the preliminary study conducted in 2012 by Kayodé et al [18] showed that there is no scientific evidence to support the traditional use of the tchoukoutou's starter named “kpètè-kpètè” in infection treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation